1977
DOI: 10.1159/000231954
|View full text |Cite
|
Sign up to set email alerts
|

Study of some Immunological Parameters in Untreated Patients with Hodgkin’s Disease

Abstract: The immunological reactivity of 40 untreated patients with Hodgkin’s disease was studied by some in vitro tests exploring the lymphocyte function, The response of lymphocytes to PHA was markedly depressed in the advanced stages of the disease, but it appeared significantly decreased also in the initial stages when a suboptimal concentration of the stimulant was used to activate the cells in culture. No significant correlation was found between the depressed lymphocyte response to PHA and a particular histologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1978
1978
1989
1989

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…In a previous paper we demonstrated that the great majority of untreated patients with HD have normal percentages of E-RFC in peripheral blood [14]. These data, which now we can confirm in another population of untreated patients with HD, are in agreement with those reported by Gajl-Peczalska et al [8] and Graze et al [9].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a previous paper we demonstrated that the great majority of untreated patients with HD have normal percentages of E-RFC in peripheral blood [14]. These data, which now we can confirm in another population of untreated patients with HD, are in agreement with those reported by Gajl-Peczalska et al [8] and Graze et al [9].…”
Section: Discussionsupporting
confidence: 92%
“…Detection of lymphocyte surface markers. E-RFC and Ig-bearing lymphocytes were detected by techniques previously reported [14].…”
Section: Methodsmentioning
confidence: 99%
“…Several investigators including us have reported the proportions and functional study of T and B lymphocytes in the peripheral blood (PB) of patients with untreated HD. Although there is general agreement that some T lymphocyte functions are impaired, a controversy exists in regard to the number of T cells evaluated by conventional surface markers, some studies reporting normal (10,11,26) and others reduced values (9,14) of E-rosette forming cells (E-RFC) in the PB of untreated patients with HD. An altered proportion of T lymphocyte subsets showing receptor for IgG (Ty) or for IgM (Tp) has also been demonstrated in HD (12,27), but subsequent studies have provided evidence that most of E-RFC having receptor for Fcy (FcyR) are not T lymphocytes (24).…”
mentioning
confidence: 99%
“…E-rosette forming cells and Ig-bearing lymphocytes were detected by techniques previously reported. 26 T cells bearing receptors for the Fc portion of IgG (TG) or IgM (T,) were determined as detailed elsehere.^"^^ TG cells were identified by rosetting purified T cells with ox red blood cells (ORBC), which had been coated with anti-ORBC rabbit IgG (EAG rosettes). After overnight incubation at 37 C in 20% fetal calf serum (FCS), T M cells were identified by rosette formation with ORBC coated with anti-ORBC rabbit IgM (EAM rosettes).…”
Section: Detection Of Lymphocyte Surface Mtrrkersmentioning
confidence: 99%